2023
DOI: 10.3390/ijerph20105774
|View full text |Cite
|
Sign up to set email alerts
|

Urban Green Spaces and Vector-Borne Disease Risk in Africa: The Case of an Unclean Forested Park in Libreville (Gabon, Central Africa)

Abstract: In Africa, vector-borne diseases are a major public health issue, especially in cities. Urban greening is increasingly considered to promote inhabitants’ well-being. However, the impact of urban green spaces on vector risk remains poorly investigated, particularly urban forests in poor hygienic conditions. Therefore, using larval sampling and human landing catches, this study investigated the mosquito diversity and the vector risk in a forest patch and its inhabited surroundings in Libreville, Gabon, central A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 69 publications
0
9
0
4
Order By: Relevance
“…During the 2006 CHIKV outbreak in the West region of Cameroon, the persistence of anti-CHIKV IgM antibodies was reported in the local population, and entomological studies revealed high relative abundance of Aedes africanus [ 9 ]. The risk of CHIKV emergence and re-emergence in the west region of Cameroon was supported by an entomological study that showed high species richness and abundance of competent vectors in this part of the country [ 40 ]. Interestingly, a study conducted at the border between Cameroon and Gabon showed that patients coming to seek health services in Kyé-ossi in Cameroon from the neighboring town of Gabon (Bitam) were diagnosed positive with CHIKV, indicating the possibility of cross-border transmission between the two countries [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the 2006 CHIKV outbreak in the West region of Cameroon, the persistence of anti-CHIKV IgM antibodies was reported in the local population, and entomological studies revealed high relative abundance of Aedes africanus [ 9 ]. The risk of CHIKV emergence and re-emergence in the west region of Cameroon was supported by an entomological study that showed high species richness and abundance of competent vectors in this part of the country [ 40 ]. Interestingly, a study conducted at the border between Cameroon and Gabon showed that patients coming to seek health services in Kyé-ossi in Cameroon from the neighboring town of Gabon (Bitam) were diagnosed positive with CHIKV, indicating the possibility of cross-border transmission between the two countries [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…albopictus and the potential risk for the transmission of arboviruses [ 51 ]. The vector ecology and competence of these two vectors of DENV has already been studied in Cameroon [ 40 , 50 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A report by Mourou et al 6 and Sevidzem et al 7 revealed a high frequency of mosquitoes in urban areas of Libreville. Other studies report outbreaks of some mosquito-borne arboviruses such as chikungunya and dengue in Libreville 8 .…”
Section: Introductionmentioning
confidence: 99%